Digital Environment as A Factor in The Formation of Responsible Behavior in Students - Gulamov Jasur Baxodirovich (International Journal Of Literature And Languages, 2026)
The article examines the problem of forming responsible behavior in students under the conditions of the digital transformation of education. It analyzes the influence of the digital environment on the development of students’ personal positions, their value orientations, and their patterns of behavior in online space. Special attention is paid to the pedagogical conditions and strategies for fostering digital responsibility among student youth. Based on the analysis of contemporary research and practical experience of working with students, the article substantiates the need for the purposeful formation of a culture of cybersecurity and digital ethics as components of the professional training of future specialists. Methodological approaches are proposed for integrating issues of responsible behavior in the digital environment into the educational process of higher education institutions.